The Realities and Barriers of Community Participation in Rural Community Development Projects : none - DIPELA, PERCY (Universitas Nahdlatul Ulama Surabaya, 2024)
This paper reports on the barriers and realities confronting community participation in community development. The paper provides possible suggestions on how inclusive participation may aid the sustainability of community development projects. Community participation refers to the involvement of individuals or groups in activities, initiatives, or decision-making processes that affect their community. It is about engaging with others to contribute ideas, resources, and efforts towards common goals and improvements within a community. This paper adopted a focused mapping review synthesis to gather the critical tenets of community participation. The author has demonstrated in this paper that community participation is mainly used as a procedural issue without really using it to canvas the views of rural community people. Mainly, it is applied as a “tick a box” exercise in which authorities do not use it to empower the community members nor adopt their views for the purpose of decision-making. Moreover, this paper demonstrates that community participation is more effective and has the potential to result in empowerment when the primacy is on training and building the capacity of beneficiaries. The author argues that community participation that is not inclusive and does not link the views of beneficiaries to decision-making is likely to result in programs that do not address the needs of beneficiaries.